Developing E-Module Based on Heyzine Flipbook in Teaching English For Elementary Students - Septiani, Astrid Nur; Nurfadhillah, Septy; Puspita, Dayu Retno (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
This research is motivated by the phenomenon of low interest in learning English among elementary school students in English subjects, which is largely caused by the use of conventional teaching materials that are less interactive and interesting. The aim of this research is to develop an interactive e-module based on Heyzine flipbook which is specifically designed to increase student involvement in the English learning process. This research uses the ADDIE model. This model consists of five stages: analysis, design, development, implementation, and evaluation. The data collection technique uses a questionnaire and is analyzed descriptively qualitatively and quantitatively. The research used test subjects with validity tests from material experts, media experts, one to one trials and small group trials. Based on the results of assessments from experts, namely media experts and material experts, with validation results, namely from material experts assessing learning media at 5, from media experts assessing learning media at 5, teacher assessments assessing learning media at 4.7, and student responses assessing learning media in one to one trials at 4.2 and small-scale trials at 4.47, thus the learning media based on the Heyzine flipbook developed is very good and worthy of being used as English learning media for elementary schools.